(untitled) (Research, Society and Development, 2023)
This article proposes an experience report on the process of bringing public Mental Health policies to the interior on the state of Pernambuco, specifically in the fifth health region during 2014 and 2018. With the objective of historicizing the path for a theoretical and practical analysis, contributions, challenges and obstacles in the articulation between the representatives of the three levels of government, especially in the municipalities, were observed, making some information relevant about the implementation of the regional network in Mental Health to the workers. The experiences and critical reflections emerge for observations that question the plastered and centralized health policies in the people who occupy the municipal health management to the detriment of the demands of the territory or in the information of the health teams. It is also possible to understand during this process of bringing of public Mental Health policies advanced, but did not mean bringing process of the anti-asylum practices recommended by the Psychiatric Reform. It is also possible to conclude that, among conflicts, tensions and discussions of care models, the suffering subject needs to be the focus of the themes of network implementation in an interdisciplinary construction of the "among several" preserving the ethical dimension in public policy.